An intriguing intracardiac mass in a woman with atrial fibrillation. Issue 9 (30th December 2015) - Chirillo, Fabio; Fusaro, Michele; Morana, Giovanni; Olivari, Zoran
Abstract : Clinical introduction: A 74-year-old hypertensive woman presented with shortness of breath. There was no associated coughing, chest pain or fever. ECG identified atrial fibrillation with rapid ventricular response. A transoesophageal echocardiogram was scheduled to exclude thrombus before cardioversion (Figure 1A); however, an echogenic structure was seen (Figure 1B arrow, see online supplementary video 1) between the left atrium, the pulmonary artery and the aortic root. Question: Which of the following is the most likely diagnosis? Aortic valve endocarditis with annular abscess Left atrial appendage thrombus Left atrial myxoma Pulmonary embolism For the answer see page 727 For the question see page 693